PERANAN KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Hecksa Manora (Edification Journal : Pendidikan Agama Islam, 2019)
Quality education really needs professional staff. Therefore professional education personnel will carry out their duties professionally to produce higher quality graduates. The type of this research is qualitative research and the method used is in-depth interview (Indepth Interview), documentation. Data analysis using this study using a Multi Case study design. The results of this study are to look at an overview of the role of principals' leadership and how the role of principals in improving the quality of education.